The effect of preemptive use of plerixafor on stem cell mobilization in patients with lymphoma and multiple myeloma - Uysal, Ayse; Erkurt, Mehmet Ali; Kuru, Irfan; Kaya, Emin; Berber, Ilhami; Sarici, Ahmet; Hidayet, Emine (Marmara Univ, Fac Medicine, 2023)
Objective: The aim of this study is to investigate the effect of the preemptive use of plerixafor in patients with lymphoma and multiple myeloma which was administered as a preemptive single dose to the patients who were determined to have a CD34+ cell count of <15/ mu L in the peripheral blood (PB) on the 4th day of mobilization.Patients and Methods: Thirty-five patients who were administered plerixafor on the 4th day after granulocyte colony-stimulating factor (G-CSF) alone for stem cell mobilization between January 2020 and November 2021 were included. CD34+ stem cell counts in PB before and after plerixafor, the amount of CD34+ stem cells collected, and the outcome of transplantation was examined.Results: The median CD34+ cell count in PB on the 4th day was 5.2/mu L (0.1-13.4), which was determined to increase 206.6-fold (31.5749347) to 924.80 /mu L (295.00-5056) following the administration of plerixafor on the 5th day (Z=-5.160; r= - 872.2; p<0.0001). The number of apheresis sessions was 1 in all patients. The median collected CD34+ cell count was 5.90x106/kg (2.70x106-14.4x106).Conclusion: The use of preemptive plerixafor shows that it is an effective mobilization method by increasing the rate of stem cell collection at an effective dose and reducing the mobilization time/apheresis sessions.
Keywords: Apheresis; Stem cell; Mobilization; Plerixafor; Preemptive